Pengelolaan BUMD Berdasarkan Prinsip Tata Kelola Perusahaan yang Baik (Good Corporate Governance) - BPHN (BPHN, 2013)
Pengelolaan BUMD Berdasarkan Prinsip Tata Kelola Perusahaan yang Baik (Good Corporate Governance)